2017
DOI: 10.1021/acs.chemmater.6b03011
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular Simulation Method To Determine Both Aluminum and Cation Location in Cationic Zeolites

Abstract: The knowledge of aluminum distribution in zeolites is a difficult task due to limitations in experimental measurements. In the present paper, we propose a new methodology to simultaneously determined aluminum atoms distribution as well as the extraframework cation location in a given experimental structure of the framework and thus allows to compared different synthesis routes. Aluminum mean distribution is obtained over a great number of configurations that are generated during the course of the simulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 93 publications
0
41
0
Order By: Relevance
“…Statistical analysis of Al distribution in ZSM‐5, MOR, and FER for typical ranges of Si/Al ratios (including 23) also show the prevalence of short‐range Al pairs in 5MR and 6MR . The distribution of Al atoms does not depend on the stability of divalent cations, as it depends on the conditions of synthesis, that is, in the presence of monovalent cations such as Na + …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Statistical analysis of Al distribution in ZSM‐5, MOR, and FER for typical ranges of Si/Al ratios (including 23) also show the prevalence of short‐range Al pairs in 5MR and 6MR . The distribution of Al atoms does not depend on the stability of divalent cations, as it depends on the conditions of synthesis, that is, in the presence of monovalent cations such as Na + …”
Section: Resultsmentioning
confidence: 90%
“…[50] The distribution of Al atoms does not depend on the stability of divalent cations,a si td ependso nt he conditions of synthesis, that is, in the presence of monovalent cations such as Na + . [51] The optimal positiona nd stabilityo fd ivalent cationss uch as Zn 2 + and Pd 2 + in mordenite have also been investigated theoreticallyb yD FT. [52][53][54] Benco et al [52] performedp eriodic DFT calculations and found that the energetically most stable Zn-MOR configurations are characterized by the presence of two Al atomsa ts hort distances. In that case, Zn 2 + is located in one of the small rings (5MR or 6MR).…”
Section: Stability Of Clean Cu Pb and Hg Sitesmentioning
confidence: 99%
“…The cubic simulation box contained one unit cell (space group Fd3m) of composition Na 58 Si 134 Al 58 O 384 (see Figure 11), corresponding to a Si/Al ratio of 2. shown that there is no preferential T-sites in faujasite zeolite. 106 Simulations were performed in the NV T ensemble with a box size of 24.679 Å, corresponding to the (experimental) unit cell at 20 • C. Initial configurations with the desired number of water molecules were first generated at 700 K, using Monte Carlo simulation with the non-polarizable force field of Jaramillo et al 29 as described in Ref. 101 Then, we used these initial configurations (at least two configurations per system to check that the final results were independent of the initial configuration) for molecular dynamics simulations with the PIM force field, equilibrating the system via simulated annealing.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The distribution of susbstitutions complies with Loewenstein's rule (-Al-O-Al-sequences are prohibited), so that they are alternated in the latter case, but is otherwise random in the former case since it was shown that there is no preferential organization in Y-faujasite. 95 Materials 30 (1999) Fig. 1.…”
Section: Simulation Detailsmentioning
confidence: 99%